PERLINDUNGAN HUKUM TERHADAP LINGKUNGAN DARI DAMPAK PERUBAHAN IKLIM DI INDONESIA BERDASARKAN PRINSIP SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Raditya Dzaky Nurseha; Akmal Bagas Athallah; Jessica Tiara Rachel Tiyaroh; Raya Nurfadjriah Ramadhani; Muhammad Adymas Hikal Fikri (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Climate change represents one of the most pressing environmental challenges facing Indonesia today. Its consequences extend beyond ecological dimensions, encompassing complex legal, social, and economic implications. This research aims to analyze the extent to which Indonesian positive law provides legal protection to the environment against the impacts of climate change, and to examine how such a legal framework aligns with the principles of the Sustainable Development Goals (SDGs), particularly SDG 13 on climate action. The findings reveal that although Indonesia has established a comprehensive legal framework — including Law No. 32 of 2009 on Environmental Protection and Management, the ratification of the Paris Agreement through Law No. 16 of 2016, and various implementing regulations — its enforcement and implementation continue to face considerable obstacles. Synchronization between national regulations and international commitments such as the SDGs and Nationally Determined Contributions (NDC) remains suboptimal, largely due to weak institutional capacity, overlapping authority, and prevailing economic interests. This study underscores the urgent need to strengthen environmental law in a manner that upholds sustainable development principles, intergenerational equity, and the integration of climate justice into Indonesia's judicial system.